Chitin-based acrylic resin and preparation method thereof
By performing acetyl treatment and reaction with organic acrylic aldehyde, a high -molecular resin is formed, and a mesh crosslinker is formed through the cross -reaction of multi -aldehyde and multi -organic amine. The problem of mesh -like cross -linking cannot be formed, which improves the strength and environmental protection after the resin formation.
Patent Information
- Application Number
- CN202411656257.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, when chitosan reacts with acrylic acid, the molecular chain of chitosan is larger and the chemical reaction activity is low. There is no chemical bond connection between chitosan, so the network crosslink cannot be formed, resulting in the film formation. The membrane strength is low.
By removing the litin through acetyl treatment, a few orbin with a smaller molecular chain is obtained, and the molecular chain surface exposes a large number of hyperthyls with high chemical reaction activity, and then reacts with organic acrylic. On the several p -massive molecular chains, and aggregate with acrylic monosterity, at the same time, the cross -reaction of multiple aldehydes and multi -organic amine is performed to form a mesh cross -linking.
The intensity of the acrylic resin has been improved, the production cost is reduced, and the burden on the environment is reduced, which is in line with the green environmental protection concept.
Smart Images

Figure CN119371614A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of high value-added utilization of biomass resources and cross-technical field of acrylic resin, and in particular relates to a chitin-based acrylic resin and a preparation method thereof. Background Art
[0002] In the mid-19th century, Germany synthesized alkyd resin. In 1912, General Electric Company of the United States used phthalic anhydride and glycerol to condense alkyd resin to replace the electrical insulation material - shellac. In 1927, RH Keenel of the United States developed a method for manufacturing alkyd resin suitable for various purposes, especially using phthalic anhydride or maleic anhydride to manufacture coating resins. In the same year, General Electric Company carried out industrial production. The output of alkyd resin coatings is very large, accounting for about 20% to 25% of the total coating industry. However, with the continuous development of human production and life, the global oil and gas resources are decreasing sharply. It is estimated that the oil resources on the earth will be exhausted within 100 years. Green and renewable bio-based materials have become the most ideal oil substitute resources and are also important new materials for the development of polymer chemical industry technology.
[0003] In the field of coating applications, bio-based materials, especially vegetable oils, have been widely used to prepare new green and environmentally friendly coatings. This is because vegetable oils have the characteristics of non-toxicity, low volatility, biodegradability, and abundant and easy-to-obtain raw materials. Since the 19th century, people have carried out a series of studies on vegetable oil-based polymers. For example, triglycerides in vegetable oils are hydrolyzed with glycerol to obtain monoglycerides for the preparation of alkyd resins; drying oils or fatty acids are first maleic anhydride-treated and then transesterified with epoxy prepolymers to prepare fatty acid-modified epoxy coatings; soybean oil is epoxidized and then combined with acrylates to prepare epoxidized soybean oil acrylate resins; monoglycerides are also a polyol that can react with diisocyanates to prepare polyurethanes. The vegetable oils used to prepare water-based polyurethanes include sunflower oil, castor oil, rapeseed oil, soybean oil, etc.; tung oil is directly formed into a biodegradable coating after thermal cross-linking polymerization. However, the demand for vegetable oils as human diets is also increasing, so the production cost of using vegetable oils as raw materials for alkyd resins is relatively high.
[0004] Chitosan, also known as chitosan or chitin, is a polysaccharide extracted from the shells of marine crustaceans. It is the second largest bio-based green resource in the world, second only to cellulose. Chitosan and its derivatives can be used as reinforcing fillers for coatings, as well as synthetic raw materials for coating resins or as film-forming substances. After deacetylation and protonation, the molecular chain of chitosan contains a large number of primary amine groups, which can easily undergo polymerization reaction with acrylic acid to form a network of molecular chains, thus improving the strength and other properties of the film after formation.
[0005] To this end, the English document "Preparation and Characterization of Hybrid Chitosan / Acrylic resin Emulsions and Their Films, Tamaki Wada et al, Macromolecular Materials and Engineering, Vol. 291, No. 7, pp. 809-819" discloses the preparation of chitosan / acrylic resin emulsion by emulsion polymerization of chitosan and acrylic acid. The specific method is to mix two emulsifiers ER-20\ER-30, deionized water, chitosan and methyl methacrylate and 2-ethylhexyl acrylate, homogenize them with a homogenizer, then add an initiator to the homogenized solution, stir at 60°C for 2 hours, and react at 70°C for two hours to obtain an emulsion. The article uses chitosan as a raw material and uses the amino group of chitosan to react with acrylic acid. However, this method has two shortcomings. First, the molecular chain of chitosan is large, and it directly reacts with acrylic acid, and the chemical reaction activity is low; second, there is no chemical bond connection between chitosans, and a network cross-linking cannot be formed, so the film strength after film formation is low. Summary of the invention
[0006] In view of the above-mentioned shortcomings, the object of the present invention is to provide a chitin-based acrylic resin and a preparation method thereof, especially using agricultural and forestry waste, i.e. shrimp shells or crab shells as raw materials, such as Figure 1 As shown, chitin is deacetylated to obtain chitin with a smaller molecular chain, and a large number of primary amino groups with high chemical reactivity are exposed on the surface of the chitin molecular chain. Organic acrylic aldehyde is further used to react with chitin, and acrylic acid groups are successfully grafted onto the chitin molecular chain and polymerized with acrylic acid monomers to form a polymer resin. At the same time, cross-reactions are carried out with polyaldehydes and polyorganic amines to generate network crosslinks, thereby improving the strength of the acrylic resin after film formation.
[0007] The specific technical solutions are as follows:
[0008] A chitin-based acrylic resin, which is composed of 30-50 parts of acrylic acid-modified chitin, 20-30 parts of acrylic acid monomer, 10-20 parts of polyaldehyde monomer, 5-10 parts of polyorganic amine, 1-5 parts of emulsifier, 0.1-0.5 parts of initiator, 0.2-0.4 parts of defoamer and 80-120 parts of deionized water by weight. The preparation method of the acrylic acid-modified chitin comprises the following steps:
[0009] S1 pretreatment: The collected shrimp shells and crab shells are washed, dried, and ground into powder to obtain crude chitosan, and then 100-300g of chitosan is soaked in a hydrochloric acid solution with a concentration of 5-8wt% and a volume of 300-500mL, and reacted for 1-3 hours at a temperature of 20-30°C and a stirring speed of 200-500 rpm, filtered, and washed with deionized water until the filtrate is neutral, and the filter residue is taken and dried at a temperature of 50°C; then, 100-300g of the dried chitosan powder is soaked in a NaOH solution with a concentration of 5-10wt% and a volume of 100-300mL. The chitosan was treated with alkali and dried for 1 to 3 hours at a temperature of 20 to 30° C. and a stirring speed of 500 to 700 rpm, and then the chitosan was filtered, washed with deionized water until the filtrate was neutral, and the residue was dried at a temperature of 50° C.; finally, 100 to 300 g of the chitosan treated with alkali and dried was immersed in a NaClO solution having a concentration of 0.3 to 0.9 wt %, and then the chitosan was reacted for 1 to 3 hours at a temperature of 20 to 30° C. and a stirring speed of 500 to 700 rpm, and then the chitosan was filtered, washed with deionized water until the filtrate was neutral, and the residue was dried at a temperature of 50° C. to obtain purified chitosan;
[0010] S2 Deacetylation: The purified chitosan powder is immersed in a NaOH solution with a concentration of 30-40wt% and a volume of 200-400mL for partial deacetylation, and 0.5-1.5g of NaBH4 is added, and the mixture is reacted at 80-90°C and a stirring speed of 500-700 rpm for 1-3 hours, filtered, and washed with deionized water until the filtrate is neutral. The residue is taken, and then 1wt% acetic acid is dripped into the residue to adjust the pH value of the chitosan suspension to 3.0-4.0, thereby obtaining a deacetylated chitosan solution, i.e., a chitin solution, which is stored at 4°C for later use.
[0011] S3 Acrylic acid modification of chitin: 10-30 parts of chitin solution, 10-20 parts of organic acrylic acid aldehyde and 2-5 parts of hydrochloric acid are added to a multifunctional reactor in sequence according to their mass proportions. The reactants are reacted at 30-40°C for 1-3 hours under a stirring speed of 500-1000 rpm. Then, NaHCO3 solution is added to neutralize the acid in the filter residue. The reaction is stopped, filtered, washed with methanol 3 times, and then washed with deionized water until the filtrate is neutral. The filter residue is taken and vacuum dried at 30-40°C to obtain acrylic acid-modified chitin.
[0012] In some of the embodiments, the acrylic acid aldehyde in S3 can be a combination of one or more of 3-formylbutenoic acid, 4-formylpentenoic acid and 5-formylhexenoic acid.
[0013] In some of the embodiments, the acrylic monomer may be a combination of one or more of n-alkyl acrylate, alkyl acrylate, acrylate, n-alkyl methacrylate, alkyl methacrylate, and methacrylate.
[0014] In some embodiments, the polyaldehyde may be a combination of one or more of glutaraldehyde, malondialdehyde, and succindialdehyde.
[0015] In some embodiments, the polyvalent organic amine may be a combination of one or more of hexamethylenetetramine, ethylenediamine, hexamethylenediamine, and diphenylmethanediamine.
[0016] In some embodiments, the emulsifier can be a combination of one or more of sodium dodecylsulfate, 2-acrylamido-methyl-propyl sodium sulfate, and 2-acrylamido-methyl-propyl ammonium sulfate.
[0017] In some embodiments, the initiator can be a combination of benzoyl peroxide and tert-butyl peroxide.
[0018] In some embodiments, the defoaming agent can be a combination of one or more of polysiloxane, GP-type glycerol polyether, and ethylene glycol siloxane.
[0019] The present invention also provides a method for preparing the chitin-based acrylic resin, which comprises the following steps:
[0020] S4 In a multifunctional reactor, acrylic acid-modified chitin, polyaldehyde monomer, emulsifier, defoamer, and deionized water are added in sequence according to the formula weight, and nitrogen is introduced while stirring at a speed of 200-500 r / min for 10-20 minutes, reacting at a temperature of 30-40°C for 0.5-1 hour, and then nitrogen is continued to be introduced for 5 minutes;
[0021] S5: Stop introducing nitrogen, add polyvalent organic amine according to the formula, and react at a temperature of 30-40°C and a stirring speed of 200-500 r / min for 0.5-1 hour;
[0022] S6: according to the formula, add acrylic acid monomer and initiator in sequence, heat to 50-60°C, adjust the stirring speed to 1000-2000r / min, keep warm for 1-2 hours, continue to introduce nitrogen to take out water vapor and remove free water, then quickly heat to 100-110°C to initiate polymerization, reflux reaction for 2-4 hours, and separate the water produced by the reaction with a water separator;
[0023] S7 After the reaction is completed, samples are taken every 30 minutes for acid value testing. When the acid value is 40-50 mg KOH / g, the reaction is stopped, the temperature is lowered to 40-50° C. and kept warm, and the mixture is dispersed for 30-60 minutes at a stirring speed of 8000-12000 r / min, and then dispersed for 30-60 minutes at a stirring speed of 1000-2000 r / min, and finally the temperature is lowered to 30° C. and filtered to obtain the chitin-based acrylic resin.
[0024] The present invention has the following advantages:
[0025] (1) Using shrimp shells and crab shells as raw materials has a low production cost and can reduce the burden on the environment caused by direct disposal of shrimp shells and crab shells;
[0026] (2) The formula does not involve the use of organic solvents, and the subsequent use of acrylic resin will not produce gases harmful to human health, which is in line with the green and environmentally friendly production concept;
[0027] (3) The present invention uses agricultural and forestry waste, i.e., shrimp shells or crab shells, as raw materials, deacetylates chitin to obtain chitin with smaller molecular chains, and exposes a large number of primary amino groups with high chemical reactivity on the surface of the chitin molecular chain. Organic acrylic aldehyde is further used to react with chitin to successfully graft acrylic acid groups on the chitin molecular chain and polymerize with acrylic acid monomers to form a polymer resin. At the same time, cross-reactions are carried out with polyaldehydes and polyorganic amines to generate network crosslinks, thereby improving the strength of the acrylic resin after film formation. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Molecular schematic diagram of the chemical reaction of chitin to prepare chitin-based acrylic resin; Figure 2 Scanning electron microscopy images of chitosan prepared in Examples 1 to 3; Figure 3 Titration curves of chitosan prepared in Examples 1 to 3.
[0029] Figure 2 Scanning electron microscopy images of chitosan prepared in Examples 1 to 3; DETAILED DESCRIPTION
[0030] The following will be combined with the drawings, technical process steps, specific implementation conditions and materials in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] The collected shrimp shells and crab shells were washed, dried, and ground into powder to obtain crude chitosan. Then, 100 g of chitosan was immersed in hydrochloric acid with a concentration of 5 wt % and a volume of 500 mL, reacted at a temperature of 30° C. and a stirring speed of 500 rpm for 3 hours, filtered, washed with deionized water until the filtrate was neutral, and the filter residue was taken and dried at a temperature of 50° C.; then, 100 g of the dried chitosan powder was immersed in a NaOH solution with a concentration of 5 wt % and a volume of 300 mL, reacted at a temperature of 30° C. and a stirring speed of 700 rpm for 3 hours, filtered, washed with deionized water until the filtrate was neutral, and the filter residue was taken and dried at a temperature of 50° C.; finally, 100 g of the chitosan treated with alkali and dried was immersed in a NaOH solution with a concentration of 0.3 wt% NaClO solution, react at a temperature of 30°C and a stirring speed of 700 rpm for 3 hours, filter, wash with deionized water until the filtrate is neutral, take the filter residue, and dry at a temperature of 50°C to obtain purified chitosan; the purified chitosan powder is immersed in a NaOH solution with a concentration of 30wt% and a volume of 400mL for partial deacetylation, and 0.5g of NaBH4 is added, react at 90°C and a stirring speed of 500 rpm for 3 hours, filter, wash with deionized water until the filtrate is neutral, take the filter residue, and then drip acetic acid with a concentration of 1wt% to adjust the pH value of the chitosan suspension to 3.6 to obtain a deacetylated chitosan solution, i.e., a chitosan solution, and the scanning electron microscope characterization results are as shown Figure 2 As shown in a, chitosan has a fibrous structure with a length of about 500 nm and a width of about 20 nm.
[0033] Example 2
[0034] The collected shrimp shells and crab shells were washed, dried, and ground into powder to obtain crude chitosan. Then, 200 g of chitosan was immersed in 400 mL of hydrochloric acid with a concentration of 6 wt % and a volume of 600 mL, and the mixture was reacted at a temperature of 25° C. and a stirring speed of 400 rpm for 2 hours. The mixture was filtered and washed with deionized water until the filtrate was neutral. The filter residue was taken and dried at a temperature of 50° C. Then, 200 g of the dried chitosan powder was immersed in 200 mL of NaOH solution with a concentration of 8 wt % and a volume of 800 mL, and the mixture was reacted at a temperature of 25° C. and a stirring speed of 600 rpm for 2 hours. The mixture was filtered and washed with deionized water until the filtrate was neutral. The filter residue was taken and dried at a temperature of 50° C. Finally, 200 g of the chitosan treated with alkali and dried was immersed in In a 0.6wt% NaClO solution, react at a temperature of 25°C and a stirring speed of 600 rpm for 2 hours, filter, wash with deionized water until the filtrate is neutral, take the filter residue, and dry at a temperature of 50°C to obtain purified chitosan; the purified chitosan powder is immersed in a 35wt% NaOH solution with a volume of 300mL for partial deacetylation, and 1g of NaBH4 is added, react at 85°C and a stirring speed of 600 rpm for 2 hours, filter, wash with deionized water until the filtrate is neutral, take the filter residue, and then drip 1wt% acetic acid to adjust the pH value of the chitosan suspension to 4.0, that is, the chitosan solution, and perform scanning electron microscopy characterization. The results are as follows Figure 2 As shown in a, chitosan has a fibrous structure with a length of about 600 nm and a width of about 22 nm.
[0035] Example 3
[0036] The collected shrimp shells and crab shells were washed, dried, and ground into powder to obtain crude chitosan. Then, 300 g of chitosan was immersed in 8 wt % hydrochloric acid with a volume of 300 mL, reacted at a temperature of 20° C. and a stirring speed of 200 rpm for 3 hours, filtered, washed with deionized water until the filtrate was neutral, and the filter residue was taken and dried at a temperature of 50° C.; then, 300 g of the dried chitosan powder was immersed in a 10 wt % NaOH solution with a volume of 300 mL, reacted at a temperature of 20° C. and a stirring speed of 500 rpm for 1 hour, filtered, washed with deionized water until the filtrate was neutral, and the filter residue was taken and dried at a temperature of 50° C.; finally, 300 g of the chitosan treated with alkali and dried was immersed in In a 0.9wt% NaClO solution, react at a temperature of 20°C and a stirring speed of 500 rpm for 1 hour, filter, wash with deionized water until the filtrate is neutral, take the filter residue, and dry at a temperature of 50°C to obtain purified chitosan; the purified chitosan powder is immersed in a 30wt% NaOH solution with a volume of 200mL for partial deacetylation, and 1.5g NaBH4 is added, react at 90°C and a stirring speed of 500 rpm for 1 hour, filter, wash with deionized water until the filtrate is neutral, take the filter residue, and then drip 1wt% acetic acid to adjust the pH value of the chitosan suspension to 3.0, that is, the chitosan solution, and perform scanning electron microscopy characterization. The results are as follows Figure 2 As shown in a, chitosan has a fibrous structure with a length of about 400 nm and a width of about 18 nm.
[0037] Example 4
[0038] Use an electronic analytical balance to accurately weigh 0.2g of chitosan powder and chitosan nano whisker samples dried to constant weight at 105℃ in a beaker, and then prepare 0.1mol / L HCl and 0.1mol / L NaOH standard solutions respectively. At 25℃, first add 20mL HCl solution to the beaker and stir magnetically for 30min to dissolve the sample, then add 30mL deionized water, insert the pH glass electrode on the Eco potentiometric titrator into the solution to be tested, and titrate with the prepared 0.1mol / L NaOH solution at the same time. The instrument automatically records the change in the pH value of the solution and the volume of the NaOH standard solution consumed during the titration process. Plot the pH value of the solution against the titration volume of the NaOH standard solution to obtain pH-V. NaOH Titration curve. Plot pH against V NaOH The first derivative curve is ΔpH-ΔV NaOH Double jump titration curve. According to the definition of deacetylation degree, the deacetylation degree is calculated according to the following formula:
[0039]
[0040] Among them, m 干重 is the mass of deacetylated chitin; V1 and V2 represent the volumes consumed by 0.1 mol / L NaOH at two inflection points; c represents the NaOH concentration; deacetylation degree and amino content w NH2 The test results are based on percentages, and each sample was tested three times to obtain the average value. Figure 3 As shown, the deacetylation degrees of chitosan prepared in Examples 1, 2 and 3 are 38.9%, 42.6% and 46.7% respectively. The results show that after deacetylation treatment, a large number of primary amino groups are exposed in the chitosan molecular chain.
[0041] Example 5
[0042] According to the mass proportions, 10 parts of chitin solution, 10 parts of 3-formylbutenoic acid and 2 parts of hydrochloric acid were added to the multifunctional reactor in sequence. The reactants were reacted at 40°C for 3 hours with a stirring speed of 500 rpm. Then, NaHCO3 solution was added to neutralize the acid in the filter residue. The reaction was stopped, filtered, washed with methanol for 3 times, and then washed with deionized water until the filtrate was neutral. The filter residue was taken and vacuum dried at 40°C to obtain acrylic acid-modified chitin.
[0043] Example 6
[0044] According to the mass proportions, 20 parts of chitin solution, 15 parts of 4-aldehyde pentenoic acid and 3 parts of hydrochloric acid were added to the multifunctional reactor in sequence. The reactants were reacted at 35° C. for 2 hours under a stirring speed of 800 rpm. Then, NaHCO3 solution was added to neutralize the acid in the filter residue. The reaction was stopped, filtered, washed with methanol for 3 times, and then washed with deionized water until the filtrate was neutral. The filter residue was taken and vacuum dried at 35° C. to obtain acrylic acid-modified chitin.
[0045] Example 7
[0046] According to the mass proportions, 30 parts of chitin solution, 20 parts of 5-formyl hexenoic acid and 5 parts of hydrochloric acid were added to the multifunctional reactor in sequence. The reactants were reacted at 30°C for 1 hour with a stirring speed of 500 rpm. Then, NaHCO3 solution was added to neutralize the acid in the filter residue. The reaction was stopped, filtered, washed with methanol for 3 times, and then washed with deionized water until the filtrate was neutral. The filter residue was taken and vacuum dried at 40°C to obtain acrylic acid-modified chitin.
[0047] Example 8
[0048] In a multifunctional reactor, acrylic acid-modified chitin, glutaraldehyde, sodium dodecylsulfate, polysiloxane and deionized water are added in sequence according to the formula weight, and stirred at a speed of 200 r / min for 20 minutes while introducing nitrogen, reacting at a temperature of 30°C for 1 hour, and then continuing to introduce nitrogen for 5 minutes; stopping the introduction of nitrogen, adding hexamethylenetetramine according to the formula amount, reacting at a temperature of 30°C and a stirring speed of 200 r / min for 1 hour; adding n-alkyl acrylate and benzoyl peroxide in sequence according to the formula amount, heating to 50°C, adjusting the stirring speed to 1000 r / min, keeping warm for 2 hours, continuing to introduce nitrogen to take out water vapor and remove free water, and then rapidly heating to 100°C to initiate polymerization reaction, reflux reaction for 4 hours, and separating the water produced by the reaction with a water separator; after the reaction is completed, taking samples every 30 minutes for acid value test, when the acid value is 40-50 mg KOH / g, stop the reaction, cool to 40°C and keep warm, disperse for 60 minutes at a stirring speed of 8000r / min, then disperse for 60 minutes at a stirring speed of 1000r / min, finally cool to 30°C, filter, and obtain the chitin-based acrylic resin.
[0049] Table 1 Raw material ratio of chitin-based acrylic resin in Example 8
[0050] Acrylic acid modified chitin 30 servings n-Alkyl acrylate 20 servings Glutaraldehyde 10 servings Hexamethylenetetramine 5 servings Sodium dodecyl sulfoxide 1 serving Benzoyl peroxide 0.1 part Polysiloxane 0.2 parts Deionized water 80 servings
[0051] The acrylic acid-modified chitin used in this example is the acrylic acid-modified chitin prepared in Example 5.
[0052] According to GB / T 6739-1996 “Coating Hardness Pencil Test Method”, the strength of the prepared chitin-based acrylic resin film (cured at 50°C for 3 hours) was tested manually. The test results showed that the film strength was >B.
[0053] The VOC of the prepared resin film was tested according to GB / T 23985-2009 “Paints and varnishes - Determination of volatile organic compound (VOC) content - Difference method”, and the result was VOC≤36.3.
[0054] The water resistance of the prepared resin film was tested according to GB / T 1727-1992. After immersion for 48 hours, the water absorption rate was 11.8%.
[0055] The tensile strength of the formed resin film (cured at 50°C for 3 hours) was tested using a universal tensile testing machine, and the film strength was 123.48 kPa.
[0056] Example 9
[0057] In a multifunctional reactor, acrylic acid-modified chitin, malondialdehyde, 2-acrylamido-methyl-propyl sodium sulfate, GP-type glycerol polyether, and deionized water are added in sequence according to the formula weight, and stirred at a speed of 300 r / min for 15 minutes while introducing nitrogen, react at a temperature of 35°C for 1 hour, and then continue to introduce nitrogen for 5 minutes; stop introducing nitrogen, add ethylenediamine according to the formula amount, react at a temperature of 35°C and a stirring speed of 300 r / min for 1 hour; add alkyl acrylate and tert-butyl peroxide in sequence according to the formula amount, heat to 55°C, adjust the stirring speed to 1500 r / min, keep warm for 1.5 hours, continue to introduce nitrogen to take out water vapor and remove free water, then quickly heat to 105°C to initiate polymerization, reflux for 3 hours, and separate the water produced by the reaction with a water separator; after the reaction is completed, take samples every 30 minutes for acid value test, and when the acid value is 40-50 mg KOH / g, stop the reaction, cool to 45°C and keep warm, disperse for 45 minutes at a stirring speed of 10000r / min, then disperse for 45 minutes at a stirring speed of 1500r / min, finally cool to 30°C, filter, and obtain the chitin-based acrylic resin.
[0058] Table 2 Raw material ratio of chitin-based acrylic resin in Example 9
[0059] Acrylic acid modified chitin 40 servings Alkyl acrylate 25 servings Malondialdehyde 15 servings Ethylenediamine 7 servings 2-Acrylamido-methyl-propyl sodium sulfate 3 servings Tert-butyl peroxide 0.3 parts GP type glycerol polyether 0.3 parts Deionized water 100 copies
[0060] The acrylic acid-modified chitin used in this example is the acrylic acid-modified chitin prepared in Example 6.
[0061] According to GB / T 6739-1996 “Coating Hardness Pencil Test Method”, the strength of the prepared chitin-based acrylic resin film (cured at 50°C for 3 hours) was tested manually. The test results showed that the film strength was >B.
[0062] The VOC of the prepared resin film was tested according to GB / T 23985-2009 “Paints and varnishes - Determination of volatile organic compound (VOC) content - Difference method”, and the result was VOC≤42.7.
[0063] The water resistance of the prepared resin film was tested according to GB / T 1727-1992. After immersion for 48 hours, the water absorption rate was 9.89%.
[0064] The tensile strength of the formed resin film (cured at 50°C for 3 hours) was tested using a universal tensile testing machine, and the film strength was 142.89 kPa.
[0065] Example 10
[0066] In a multifunctional reactor, acrylic acid-modified chitin, succinaldehyde, 2-acrylamido-methyl-propyl ammonium sulfate, ethylene glycol siloxane, and deionized water were added in sequence according to the formula weight, and nitrogen was introduced and stirred at a speed of 500 r / min for 10 minutes. The reaction was carried out at a temperature of 40°C for 0.5 hour, and then nitrogen was introduced for 5 minutes. The introduction of nitrogen was stopped, diphenylmethanediamine was added according to the formula amount, and the temperature was 40°C and the stirring speed was 500 r / min. min, react for 0.5 hour; according to the formula amount, methacrylate and benzoyl peroxide are added in sequence, the temperature is raised to 60°C, the stirring speed is adjusted to 2000r / min, the temperature is kept for 1 hour, nitrogen is continuously introduced to take out water vapor and remove free water, and then the temperature is quickly raised to 110°C to initiate polymerization reaction, and the reflux reaction is performed for 2 hours, and the water produced by the reaction is separated by a water separator; after the reaction is completed, samples are taken every 30 minutes for acid value test, when the acid value is 40-50mg KOH / g, the reaction is stopped, the temperature is lowered to 40-50°C and kept warm, dispersed for 30 minutes at a stirring speed of 12000r / min, and then dispersed for 30 minutes at a stirring speed of 2000r / min, and finally cooled to 30°C, filtered, and the chitin-based acrylic resin is obtained.
[0067] Table 3 Raw material ratio of chitin-based acrylic resin in Example 10
[0068] Acrylic acid modified chitin 50 servings Methacrylate 30 servings Succinaldehyde 20 servings Diphenylmethanediamine 10 servings 2-Acrylamido-methyl-propylammonium sulfate 5 servings Benzoyl peroxide 0.5 serving Ethylene glycol siloxane 0.4 parts Deionized water 120 servings
[0069] The acrylic acid-modified chitin used in this example is the acrylic acid-modified chitin prepared in Example 7.
[0070] According to GB / T 6739-1996 “Coating Hardness Pencil Test Method”, the strength of the prepared chitin-based acrylic resin film (cured at 50°C for 3 hours) was tested manually. The test results showed that the film strength was >B.
[0071] The VOC of the prepared resin film was tested according to GB / T 23985-2009 “Paints and varnishes - Determination of volatile organic compound (VOC) content - Difference method”, and the result was VOC≤50.9.
[0072] The water resistance of the prepared resin film was tested according to GB / T 1727-1992. After immersion for 48 hours, the water absorption rate was 8.76%.
[0073] The tensile strength of the formed resin film (cured at 50°C for 3 hours) was tested using a universal tensile testing machine, and the film strength was 123.48 kPa.
[0074] Embodiment 11
[0075] The process parameters were the same as those in Example 8, and the formula remained the same except that glutaraldehyde and hexamethylenetetramine in Example 8 were not added.
[0076] The tensile strength of the formed resin film (cured at 50°C for 3 hours) was tested using a universal tensile testing machine, and the film strength was 79.68 kPa.
[0077] Example 12
[0078] The process parameters were the same as those in Example 9, and the formula remained the same except that malondialdehyde and ethylenediamine in Example 9 were not added.
[0079] The tensile strength of the formed resin film (cured at 50°C for 3 hours) was tested using a universal tensile testing machine, and the film strength was 89.71 kPa.
[0080] Embodiment 13
[0081] The process parameters were the same as those in Example 10, and the formula remained the same except that succinaldehyde and diphenylmethanediamine in Example 10 were not added.
[0082] The tensile strength of the formed resin film (cured at 50°C for 3 hours) was tested using a universal tensile testing machine, and the film strength was 72.56 kPa.
[0083] By comparing the membrane strengths of Example 8 and Example 11, Example 9 and Example 12, and Example 10 and Example 13, it can be seen that the introduction of polyaldehydes and organic polyamines can promote the formation of network cross-links between chitin molecules and improve membrane strength.
[0084] Technical personnel should note that although the present invention has been described according to the above specific implementation methods, the inventive concept of the present invention is not limited to this invention, and any modification using the inventive concept will be included in the scope of protection of this patent.
Claims
1. A chitin-based acrylic resin, characterized in that The chitin-based acrylic resin is composed of 30-50 parts of acrylic acid-modified chitin, 20-30 parts of acrylic acid monomer, 10-20 parts of polyaldehyde monomer, 5-10 parts of polyorganic amine, 1-5 parts of emulsifier, 0.1-0.5 parts of initiator, 0.2-0.4 parts of defoamer and 80-120 parts of deionized water by weight. The preparation method of acrylic acid-modified chitin comprises the following steps: S1 pretreatment: The collected shrimp shells and crab shells are washed, dried, and ground into powder to obtain crude chitosan, and then 100-300g of chitosan is soaked in a hydrochloric acid solution with a concentration of 5-8wt% and a volume of 300-500mL, and reacted for 1-3 hours at a temperature of 20-30°C and a stirring speed of 200-500 rpm, filtered, and washed with deionized water until the filtrate is neutral, and the filter residue is taken and dried at a temperature of 50°C; then, 100-300g of the dried chitosan powder is soaked in a NaOH solution with a concentration of 5-10wt% and a volume of 100-300mL. The chitosan was treated with alkali and dried for 1 to 3 hours at a temperature of 20 to 30° C. and a stirring speed of 500 to 700 rpm, and then the chitosan was filtered, washed with deionized water until the filtrate was neutral, and the residue was dried at a temperature of 50° C.; finally, 100 to 300 g of the chitosan treated with alkali and dried was immersed in a NaClO solution having a concentration of 0.3 to 0.9 wt %, and then the chitosan was reacted for 1 to 3 hours at a temperature of 20 to 30° C. and a stirring speed of 500 to 700 rpm, and then the chitosan was filtered, washed with deionized water until the filtrate was neutral, and the residue was dried at a temperature of 50° C. to obtain purified chitosan; S2 deacetylation: the purified chitosan powder is immersed in a NaOH solution with a concentration of 30-40wt% and a volume of 200-400mL for partial deacetylation, and 0.5-1.5g of NaBH4 is added, and the mixture is reacted at 80-90°C and a stirring speed of 500-700 rpm for 1-3 hours, filtered, and washed with deionized water until the filtrate is neutral, the filter residue is taken, and then acetic acid with a concentration of 1wt% is dripped into the chitosan suspension to adjust the pH value to 3.0-4.0, thereby obtaining a deacetylated chitosan solution, i.e., a chitin solution, which is stored in a 4°C environment for standby use; S3 Acrylic acid modification of chitin: 10-30 parts of chitin solution, 10-20 parts of organic acrylic acid aldehyde and 2-5 parts of hydrochloric acid are added to a multifunctional reactor in sequence according to their mass proportions. The reactants are reacted at 30-40°C for 1-3 hours under a stirring speed of 500-1000 rpm. Then, NaHCO3 solution is added to neutralize the acid in the filter residue. The reaction is stopped, filtered, washed with methanol 3 times, and then washed with deionized water until the filtrate is neutral. The filter residue is taken and vacuum dried at 30-40°C to obtain acrylic acid-modified chitin.
2. The chitin-based acrylic resin according to claim 1, characterized in that The organic acrylic aldehyde in S3 can be a combination of one or more of 3-formylbutenoic acid, 4-formylpentenoic acid and 5-formylhexenoic acid.
3. The chitin-based acrylic resin according to claim 1, wherein The acrylic monomer may be a combination of one or more of n-alkyl acrylate, alkyl acrylate, acrylate, n-alkyl methacrylate, alkyl methacrylate, and methacrylate.
4. The chitin-based acrylic resin according to claim 1, characterized in that The polyaldehyde may be a combination of one or more of glutaraldehyde, malondialdehyde and succindialdehyde.
5. The chitin-based acrylic resin according to claim 1, wherein The polyvalent organic amine may be a combination of one or more of hexamethylenetetramine, ethylenediamine, hexamethylenediamine, and diphenylmethanediamine.
6. The chitin-based acrylic resin according to claim 1, characterized in that The emulsifier may be a combination of one or more of sodium dodecylsulfate, sodium 2-acrylamido-methyl-propyl sulfate, and ammonium 2-acrylamido-methyl-propyl sulfate.
7. The chitin-based acrylic resin according to claim 1, characterized in that The initiator can be a combination of benzoyl peroxide and tert-butyl peroxide.
8. The chitin-based acrylic resin according to claim 1, characterized in that The defoaming agent can be a combination of one or more of polysiloxane, GP type glycerol polyether, and ethylene glycol siloxane.
9. The method for preparing a chitin-based acrylic resin according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S4 In a multifunctional reactor, acrylic acid-modified chitin, polyaldehyde monomer, emulsifier, defoamer, and deionized water are added in sequence according to the formula weight, and nitrogen is introduced while stirring at a speed of 200-500 r / min for 10-20 minutes, reacting at a temperature of 30-40°C for 0.5-1 hour, and then nitrogen is continued to be introduced for 5 minutes; S5: Stop introducing nitrogen, add polyvalent organic amine according to the formula, and react at a temperature of 30-40°C and a stirring speed of 200-500 r / min for 0.5-1 hour; S6: according to the formula, add acrylic acid monomer and initiator in sequence, heat to 50-60°C, adjust the stirring speed to 1000-2000r / min, keep warm for 1-2 hours, continue to introduce nitrogen to take out water vapor and remove free water, then quickly heat to 100-110°C to initiate polymerization, reflux reaction for 2-4 hours, and separate the water produced by the reaction with a water separator; S7 After the reaction is completed, samples are taken every 30 minutes for acid value testing. When the acid value is 40-50 mg KOH / g, the reaction is stopped, the temperature is lowered to 40-50° C. and kept warm, and the mixture is dispersed for 30-60 minutes at a stirring speed of 8000-12000 r / min, and then dispersed for 30-60 minutes at a stirring speed of 1000-2000 r / min, and finally the temperature is lowered to 30° C. and filtered to obtain the chitin-based acrylic resin.
Citation Information
Cited By
Chitin-based acrylic resin and preparation method thereof
CN120059092A
Bio-based water-based coating and preparation method thereof
CN120590870A
A bio-based water-based coating and its preparation method
CN120590870B